Avian influenza overview December 2022 – March 2023. (20th March 2023) - ,; ,; ,; Adlhoch, Cornelia; Fusaro, Alice; Gonzales, José L; Kuiken, Thijs; Marangon, Stefano; Mirinaviciute, Grazina; Niqueux, Éric; Stahl, Karl; Staubach, Christoph; et al.
Abstract: Between 3 December 2022 and 1 March 2023 highly pathogenic avian influenza (HPAI) A(H5N1) virus, clade 2.3.4.4b, was reported in Europe in domestic (522) and wild (1, 138) birds over 24 countries. An unexpected number of HPAI virus detections in sea birds were observed, mainly in gull species and particularly in black‐headed gulls (large mortality events were observed in France, Belgium, the Netherlands, and Italy). The close genetic relationship among viruses collected from black‐headed gulls suggests a southward spread of the virus. Moreover, the genetic analyses indicate that the virus persisted in Europe in residential wild birds during and after the summer months. Although the virus retained a preferential binding for avian‐like receptors, several mutations associated to increased zoonotic potential were detected. The risk of HPAI virus infection for poultry due to the virus circulating in black‐headed gulls and other gull species might increase during the coming months, as breeding bird colonies move inland with possible overlap with poultry production areas. Worldwide, HPAI A(H5N1) virus continued to spread southward in the Americas, from Mexico to southern Chile. The Peruvian pelican was the most frequently reported infected species with thousands of deaths being reported. The reporting of HPAI A(H5N1) in mammals also continued probably linked to feeding on infected wild birds. In Peru, a mass mortality event of sea lions was observed in January and February 2023. Since October 2022, six A(H5N1) detections in humans were reported from Cambodia (a family cluster with 2 people, clade 2.3.2.1c), China (2, clade 2.3.4.4b), Ecuador (1, clade 2.3.4.4b), and Vietnam (1, unspecified clade), as well as two A(H5N6) human infections from China. The risk of infection with currently circulating avian H5 influenza viruses of clade 2.3.4.4b in Europe is assessed as low for the general population in the EU/EEA, and low to moderate for occupationally or otherwise exposed people.